Crisis Communication in Bali's Tourism Industry in Dealing With the Issue of Over Tourism - Agnesia Hervina Tiaraningrum; Ridy Sulhana; R. Raditya Wira Fabri (Lembaga Pengembangan Kinerja Dosen, 2026)
Overtourism has emerged as a emergd as a structural crisis in many tourism destinations, including Bali, driven by post-pandemic visitation growth, media amplification, and limited destination carrying capacity. This condition has intensified environmental, social, and reputational pressures, necessitating that tourism stakeholders adopt effective crisis communication strategies. This study aims to analyze crisis communication practices employed by the tourism industry in Bali in addressing overtourism issues, identify the roles of key stakeholders, and evaluate the implications of media and digital communication in shaping public perceptions. Using a qualitative approach, data were collected through in-depth interviews with government officials, tourism industry actors, and local community representatives, complemented by field observations and document analysis. The data were analyzed thematically to identify patterns of crisis narratives, coordination mechanisms, and communication strategies. The findings indicate that crisis communication in Bali is increasingly characterized by collaborative governance, transparency-oriented messaging, and the strategic use of digital platforms to manage public discourse. Media framing and user-generated content were found to significantly influence the escalation of overtourism as a reputational crisis, while coordinated communication among stakeholders helped mitigate negative perceptions and support sustainable tourism policies. This study concludes that effective crisis communication plays a critical role not only in managing overtourism-related crises but also in strengthening destination resilience and long-term sustainability.